Determinantes da taxa real de câmbio de longo prazo: teoria e evidência - Lucio Otavio Seixas Barbosa (2017)
This dissertation presents a new framework for the determinants of real exchange rate in the long-run in developing and emerging countries (DECs) from a post-Keynesian approach. Such model assumes that currencies should be regarded as an asset. In consequence, dealers in the foreign exchange market play a crucial role on its dynamics, especially the process by which agents form expectations. Furthermore, according to Keynes own-rate of interest asset theory in his General Theory of Employment, Interest and Money (GT), currency has the followings attributes: yield, carrying costs, expected appreciation and international liquidity premia (currencies or financial instruments carrying costs are significantly low, thereby they can be disregarded). Among them, we highlight liquidity premia. Considering the hierarchical international monetary system nature, nonconvertible currencies have lower liquidity premia since they are not used for international payments. Hence, on one hand, external liabilities prevent DECs currency to act as a stable unit due to its volatility; on the other hand, it demands foreign currency to repay it. Thereby, the ability to trigger cash flows through commercial transactions is relevant. In this context, productivity differential may signalize countries potential to circumvent the lack of foreign exchange. In addition, it affects non-tradable goods prices, contributing to appreciate the real exchange rate. Thus, the theoretical framework encompass real and financial factors as drivers of the real exchange rate in the long-run. The empirical results endorse such approach, pointing out i) financial factors supremacy, ii) ambiguous behave of variables associated with international liquidity, current account surplus and interest rate differential, iii) model inadequacy to deal with developed countries. In what follows, we analyses macroeconomic policies capable of influencing long-run real exchange rate, which is considered as a key variable to prompt growth under a nonconventional literature. In this vein, we identify economic policy tools that can devalue it. After discussing the trilema, we analyze those variables that could affect real exchange rate without constraining monetary policy or exchange regime choice, which are foreign exchange intervention, capital control and macroeconomic policy coordination. This last one comprise fiscal and wages policy to avoid non-tradable prices inflation, as well as wage increases above productivity growth. The results suggest that the relative progress experienced by Asian countries was enable by foreign exchange rate interventions and, possibly, by capital account openness combined with an export-led growth strategy. In contrast, Latin American misfortune was based on foreign exchange rate interventions ineffectiveness, current account openness without any strategy and lack of macroeconomic policy coordination via fiscal surplus. Therefore, if Latin American countries want to take a similar route of Asian ones, they should enlarge its international reserves and cut their interest rate to set up foreign exchange rate interventions, increase capital control and curtail government spending on non-tradable goods.